The implementation of quality management system (ISO 9001) in analysing the workmanships performance in selected projects - Chong, Chuan Yee (2006)
This study describes on the implementation of Quality Management System (ISO 9001) in analysing the workmanships performance in selected projects. Two projects of different nature, which consists of medium cost low rise housing and low medium cost apartments projects selected in ISO 9001 certified organization found to be perform better in workmanships compare to non ISO 9001 certified organization. This is due to the fact that in non ISO certified organization, there are problems related to documentation and management. This is critical as the three most significant factors that contribute to poor construction workmanships identified are poor documentation, poor performance of workers and poor management. Hence, this study indicates that ISO 9001 certified organization could produce more quality workmanships construction projects than non ISO 9001 certified organization. The study reveals fewer defect recorded in ISO certified organization